Effect of stabilizers on stiffness modulus of soil layers: a review - Moazami, Dariush; Md Yusoff, Zainuddin; Muniandy, Ratnasamy; Hamid, Hussain (Academic Journals, 2013)
Subgrade layer has a significant contribution in the pavement structure, and the quality of this layer has a great impact on the subsequent pavement design. Pavement design guide as specified in the AASHTO (2002), incorporates engineering properties of unbound and stabilized subgrade soils, since in many cases fatigue or rutting failure in pavements are due to insufficient stiffness modulus in soil layers. Subgrade materials are characterized by common engineering properties including stiffness and strength. Appropriate treatment using different additives is considered an effective way to achieve a more durable pavement structure and also to increase the stiffness modulus. In this paper, the importance of using proper stiffness for underlying layers and the effects of common additives such as lime, cement and fly ash on improving the strength and stiffness modulus of soil layers are highlighted.